THE USE OF ANTIBIOTICS IN THE DENTAL FIELD – THE PHENOMENON OF ANTIBIOTIC RESISTANCE - Alina Anton; Iasmina Alexandra Predescu; Nuca Cristina; Mariana Păcurar; Ștefania Dinu (Romanian Journal of Oral Rehabilitation)
Antibiotics are one of the most important discoveries of the 20th century, widely used in the dental field for prophylactic or therapeutic scope, treating non-odontogenic and odontogenic acute and chronic infections. Antimicrobial resistance is an alarming problem that involves important consequences, especially in managing therapies for patients with life-threatening infections. In the dental field, antibiotic consumption is not always considered adequate, leading to incorrect or excessive drug use. This phenomenon is reflected in the therapeutic failure observed in many cases. The apparition of microbial biofilms, such as dental plaque, may be an important reason for promoting antibiotic resistance. The antimicrobial resistance increases usually with repeated cycles of AB administration for the selection of microorganisms. Phytotherapy represents an undeniable source of therapeutic solutions for various pathologies, including bacterial contamination. Thus, the effect of antimicrobial resistance can be reduced by replacing common antibiotics with phytocompounds, if this switch is admissible.